Culture, humility and the law: Towards a more transformative teaching framework. (June 2017) - Hamman, Evan
Cultural competency has proven less effective than its proponents had envisioned. Disciplines outside of the law (social work, health and psychology) have turned to the more powerful theory of 'cultural humility' – a framework for lifelong learning and self-reflection. Cultural humility contends that one can never really 'master' another's culture, but that we ought to remain respectful and reflective in our approach. In this article I make the case for teaching cultural humility in Australian law schools.